Optical Properties and Dynamic Extrinsic Chirality of Structured Monolayer Black Phosphorus - Sun, Mengke; Wang, Ying; Hu, Hui; Zhang, Hao; Li, Wenjia; Lv, Bo; Zhu, Zheng; Guan, Chunying; Shi, Jinhui (Frontiers in Materials, 2022)
Chiral metamaterials have drawn increasing attention due to their strong chiral responses. The monolayer black phosphorus is a tunable two-dimensional material with anisotropy that plays an important role in a variety of fields such as chirality and polarization control. In this work, we propose a metamaterial with structured monolayer black phosphorus to manipulate the transmission properties of circularly polarized waves. The metamaterial exhibits strong circular dichroism and circular birefringence effects depending on oblique incidence of circularly polarized wave and has a weaker circular conversion dichroism effect as well. Moreover, this work also investigates effects of different chiral phenomena of the metamaterial on various structural parameters as well as incident angles and the electron concentration. It has been proved the electron concentration of monolayer black phosphorus can effectively tune the chirality properties. Particularly, the pure optical activity always occurs regardless of the elevation angle and the azimuthal angle. The proposed framework provides opportunities for designing meta-devices with monolayer black phosphorus and practical potentials for novel and high-performance infrared metamaterials.